(3TQM JSgjd GdahGFO hJcejd GdebGUOs - (3eMeO Hf YHO Gddg, GHf eGdc GdWGFj GdLqjGfj, CHh YHO Gddg, LeGd GdOjf,J (B672 (3g` s
(3ChdgG (B:s
(3bGd GdTjN GHf eGdc GdWGFi GdCfOSi MGeOkG ddg CeG HYO aEf HYV GdaVdGA SCdfi Cf CTaY cJGHi GdeSei HJSgjd GdahGFO s
(3BNQgG (B:s
(3hbO jbGd (B: (3dGShi HeYfi dGSjeG gfG GfJgi GdSaQ GdChd ef TQM GdJSgjd deDdag QMeI Gddg JYGdi jJdhg ai GdKGfi HGH GdMGd s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B223 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B130s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdfMhs